Single-fed Ku/Ka dual-band aperture shared planar antenna array for satellite communication - Kim, Jeong Wook; Oh, Seung Won; Lee, Han Lim (Alexandria Engineering Journal, 2024)
This paper presents a single-fed Ku/Ka dual-band aperture-shared planar antenna array designed for satellite communication. The need to enhance data transmission speeds has driven the exploration of higher frequency bands, such as the Ku-band and Ka-band. Researchers have been investigating the design of multiband antennas to achieve space miniaturization and cost-effectiveness in these higher frequency bands. However, previous works faced challenges, including spatial efficiency limitations, complex radiator structures, band isolation issues, and increased complexity in the feeding network. To address the abovementioned challenges, this paper proposes a single-fed Ku/Ka dual-band shared-aperture planar antenna array. By combining a patch antenna for the Ku-band and a cavity antenna for the Ka-band, a simple and single-fed network is realized. The proposed antenna element is further extended to a linear array antenna and a sequentially rotated array antenna. The implemented sequentially rotated array antenna exhibited a measured impedance bandwidth of 17.4–19.7 GHz (12.4%) and 27.0–29.0 GHz (7.1%). Moreover, the proposed sequentially rotated array antenna demonstrated measured peak gains of 13.7 dBi for right-hand circular polarization in the Ku-band receiver and a measured peak gain of 15.6 dBi for left-hand circular polarization in the Ka-band transmitter, making it highly suitable for satellite communication.
Keywords: Aperture antennas; Dual Band; Dual band antennas; Ku band; Planar antenna arrays; Satellite communications; Shared aperture; Shared-aperture antenna; Single feeds; Single-feed ku/ka dual-band antenna; Circular polarization; Satellite communication; Shared-aperture antenna; Single-fed Ku/Ka dual-band antenna